Democratic Adult Education in United States - Tellado Itxaso (Social and Education History, 2012)
Democracy in adult education promotes an outstanding organizational practice for adult learning centers. Regularly, low literate, workingclass people, and Black individuals were excluded of political decisions and learning opportunities of the adult learning organizations they attend. This paper focused on adult learners’ participation in an adult school in the South of the United States, Highlander Folk School. Learners and educators are engaged in all the school decisions to overcome social inequalities. The involvement of learners in decisionmaking teams is essential to the success of shared governance and other participative structures and, is one of the aspects that explain the higher levels of participation in the school. The paper is centered on the strategies used within the community organization for the implementation of democratic adult educational practices and how those successful experiences help the overcoming of social exclusion.